Flexible Ti3C2Tx/Graphene Films with Large‐Sized Flakes for Supercapacitors. Issue 7 (13th May 2021) - Guo, Tiezhu; Fu, Maosen; Zhou, Di; Pang, Lixia; Su, Jinzhan; Lin, Huixing; Yao, Xiaogang; Sombra, Antonio Sergio Bezerra
Abstract : The new 2D Ti3 C2 T x MXene material is widely studied in the field of supercapacitors. However, the electrochemical performance is discounted due to Ti3 C2 T x film's compact self‐stacking phenomenon. Therefore, the synthesized flexible self‐supporting Ti3 C2 T x /graphene composite membrane effectively alleviates this inherent disadvantage. Unlike using the traditional reduction graphene oxide, the structural integrity and large‐sized flakes of graphene are synthesized through anhydrous ferric chloride (FeCl3 )‐intercalated natural graphite flakes; the obtained composite membrane with high electron transfer capability due to graphene and Ti3 C2 T x nanosheets shows fewer defects and faster electrolyte ion transport kinetics due to high porosity and specific surface area. The assembled self‐supporting binder‐free symmetric supercapacitor shows an ultrahigh gravimetric energy density of 13.1 Wh kg −1 at a power density of 75 W kg −1 . Herein, a new perspective for the mechanism analysis of inhibiting self‐stacking of MXene is provided. Abstract : The structural integrity and large‐sized flakes of graphene are synthesized through anhydrous ferric chloride (FeCl3 )‐intercalated natural graphite flakes. The introduction of graphene into Ti3 C2 T x improves the specific capacitance, mainly due to the improvement of specific surface area rather than the interlayer spacing. Specifically, graphene is freely distributed in Ti3 C2 T x .